Bourgeois? Public? Sociable? : Habermas and Koselleck on civil society (Sociologisk Forskning, 2024)
Habermas’ work on the “bourgeois public sphere” was published more than sixty years ago and had a major international impact. The author himself has recently commented on the study’s encounter with contemporary media landscapes and society. Habermas, and many with him, still see the decay of later modern civil society as a threat to its potential as infrastructure for publicity, civility and discursive democracy. Koselleck’s classical study of the Enlightenment preceded Habermas, but warned against utopianism, “despotic moralism” and held that irresponsible criticism could be the consequences of enlightened public discourses. Habermas’ more influential analysis speaks of an uncompleted modernity and continues to defend a rational public sphere in the spirit of Kant’s Enlightenment. Koselleck warned against the completion of the Enlightenment in which he judged Freemasons to be far more active promoters than Habermas, but Koselleck’s political position in this is still subject to interpretation and criticism. This articlesets the two approaches in relation to each other and tries to clarify Koselleck’s position. Both similarities and differences are highlighted. Finally, the issue of what is fruitful and what needs to be reformulated are discussed.
Keywords: Habermas; Koselleck; civil society; public sphere; freemasonry